Nursing work: analysis of wage trends in Brazil (Research, Society and Development, 2021)
The scope of the study was to analyzes the trends in the remuneration of the work of nursing professionals, including those with higher and secondary education. This is a cross-sectional study that used data from the Annual List of Social Information (Relação Anual de Informações Sociais - RAIS), which compiles information on labor activity in the country, thus enabling the identification of the difference between the remunerations of nursing professionals with higher education and those with secondary education in the years 2003 and 2018 in Brazil. The variables 2002 Brazilian Classification of Occupations (Classificação Brasileira de Ocupações - CBO 2002), number of hours hired and the value of the average nominal remuneration were analyzed and the financial values were corrected ​​by the Broad Consumer Price Index. The remuneration of nurses and technicians over the past 15 years. There is a slight stagnation in the amount received by nurses and a real increase in the amount received by technicians, which accompanied the minimum wage. The composition of workers with a weekly workload of 40 to 44 hours has changed. There was an expansion of 94.9% in the number of bonds between 2003 (350,470) and 2018 (682,532) and a change in the proportion between groups. In 2003, 84.4% were technicians and 15.6% were nurses. In 2018, 71.4% were technicians and 28.6% were nurses. There is a trend towards an approximation between remunerations of the nursing staff and a relative decrease in the number of technicians and a relative increase in the number of nurses.